Occurrence of sleep-related breathing disorders in patients with chronic urticaria at its asymptomatic or oligosymptomatic stages - Perkowska, Jolanta; Kruszewski, Jerzy; Gutkowski, Piotr; Chciałowski, Andrzej; Kłos, Krzysztof (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2016)
Introduction : Chronic urticaria (CU), in view of its manifestations (pruritus, wheals), chronic and recurrent nature is very bothersome for patients and significantly influences their quality of life. Aim : To assess the importance of sleep problems and sleep-related breathing disorders (SRBDs) declared by CU patients, for their quality of life. Material and methods : Twenty-eight patients with CU at an asymptomatic stage or with minimal symptoms and signs were qualified for the study. In these patients, assessment of urticaria severity, QoL and SRBDs incidence was carried out. Results : In a questionnaire study (CU-Q2oL), about 54% of the patients with CU complained of sleeping problems, about 80% reported significant fatigue and lack of concentration in the daytime. Respiratory polygraphy, an objective measure of sleep-related breathing disorders (SRBDs) demonstrated their higher incidence in patients with CU than in the general population, but these disorders were mild and had no influence on the reduced quality of life of the study patients, compared with a group of patients without SRBDs. Conclusions : The occurrence of SRBDs was found in 25% of patients with CU at asymptomatic or oligosymptomatic stages. The SRBDs in those patients were mild, required no treatment and their occurrence did not cause any significant reduction in their quality of life.